Agile Development in the Real World - Cline, Alan. (Apress : Imprint: Apress, 2015)
This book is a practical guide for new agile practitioners and contains everything a new project manager needs to know to get up to speed with agile practices quickly and sort out the hype and dogma of pseudo-agile practices.The author lays out the general guidelines for running an agile project with the assumption that the project team may be working in a traditional environment (using the waterfall model, or something similar). Agile Development in the Real World conveys valuable insights to multiple audiences: For new-to-agile project managers, this book provides a distinctive approach that Alan Cline has used with great success, while showing the decision points and perspectives as the agile project moves forward from one step to the next. This allows new agile project managers or agile coaches to choose between the benefits of agile and the benefits of other methods. For the agile technical team member, this book contains templates and sample project artifacts to assist in learning agile techniques and to be used as exemplars for the new practitioner’s own project. For the Project Management Office (PMO), the first three chapters focus on portfolio management. They explain, for the agilists’ benefit, how projects are selected and approved, and why projects have an inherent "shelf-life" that results in hard deadlines that may seem arbitrary to traditional technical teams.